Provision of Local Food-Based Formula Using Pila Ampullacea, Tempeh, and Moringa Oleifera Leaves to the Acceptability and Nutrition Intake in Hemodialysis Patients - Fery Lusviana Widiany; Mochammad Sja’bani; Susetyowati Susetyowati; Emy Huriyati (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2022)
Background: One of the actions that can be taken to overcome malnutrition in hemodialysis is to improve nutrient intake. It is necessary to provide local food-based formula using Pila ampullacea, tempeh with local soybean, and Moringa oleifera leaves for hemodialysis patients.Objective: To analyze the effect of local food-based formula using Pila ampullacea, tempeh, and Moringa oleifera leaves to the acceptability and nutrition intake in hemodialysis patients.Materials and Methods: This study was carried out in Dr. Sardjito Hospital, Yogyakarta, Indonesia from February to March 2020. Subjects were 54 maintenance hemodialysis patients who met the criteria of study. The independent variable was the provision of local food-based formula, while the dependent variable were the acceptability and nutrition intake.Results: As many as 42.59% of subjects were able to consume all the formula given for three days and 50% of subjects have good acceptance of the local food-based formula. The effect of formula intake to the total intake of energy, carbohydrates, fiber, water, calcium, phosphorus, iron showed p-value <0.05, but p-value ≥0.05 for protein, fat, sodium, and potassium. The effect of the non-formula intake to the total intake for all nutrients showed p-value <0.05.Conclusion: Most of the subjects have a good acceptance of the local food-based formula. Formula intake affects total intake of energy, carbohydrates, fiber, water, calcium, phosphorus, and iron, but does not affect total intake of protein, fat, sodium, and potassium. The total intake for all nutrients was affected by the subject's intake of non-formula sources.